Role of helmets in blast mitigation: insights from experiments on PMHS surrogate. (2016) - Ganpule, Shailesh; Salzar, Robert; Perry, Brandon; Chandra, Namas
Blast induced traumatic brain injury (bTBI) has emerged as the most significant injury to war fighters in recent conflicts. Interaction of the blast wave with the head and helmet are not well understood. In this work, the effects of blast were investigated on the post-mortem human subject (PMHS) head using a compression driven shock tube. The results suggest that the evolution of intracranial pressure profiles is strongly governed by the wave propagation through skin-skull-brain parenchyma. It is also observed that the sinus cavities naturally attenuate the blast overpressure. Performance of two helmet configurations (padded and suspension) in mitigating the blast is also evaluated. The results suggest that the amount of mitigation offered by each helmet varies with the helmet configuration. For helmets with the suspension system, the blast wave is intensified beneath the helmet. Further, the degree of blast wave mitigation is affected by the morphology of the PMHS itself. Overall, these results suggest that the blast wave interacts with the head and the helmet in a complex manner and these interaction effects must be taken into account while designing strategies for protection of the head against the blast.